Laser Welding of Aluminium Alloys - Kvasnova, Petra; Novak, Daniel; Novak, Viktor (Manufacturing Technology Journal, 2017)
Laser beam welding is an industrial technology that has seen a significant development from the early stages up to the present. Technological process management ensures high product quality as well as enhanced productivity and competitiveness. The aim of the research is to determine the impact of welding parameters by fiber laser beam on the quality of weld joints from aluminium. Basing on the presented quality assessment methods and computer simulation, we evaluate the weld joint samples. Finally, we discuss optimal welding parameters and conditions allowing the production of weld joints of the desired properties.
Keywords: Pure aluminium; Welding; Fiber Laser; Microscopy; Computer simulation